Prototype of Knowledge Management System for the Higher Education Institution in Indonesia - Ilyas Nuryasin; Yudi Prayudi; Teduh Dirgahayu (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2013)
In this paper, we propose a model of knowledge management for higher education institution in Indonesia. The model consists of five processes (i.e. capturing, structuring, storing, disseminating and implemetation) and six critical success factors (i.e. vision, culture, management support, technology, education and motivation, and maintenance). Based on the model, we develop a prototype of knowledge management system that accomodates activities and processes in higher education institutions. The prototype is designed to support organization learning and can be used as knowledge repository in the organization.